NADH dehydrogenases drive inward electron transfer in Shewanella oneidensis MR‐1. Issue 3 (24th November 2022) - Tefft, Nicholas M.; Ford, Kathryne; TerAvest, Michaela A.
Abstract: Shewanella oneidensis MR‐1 is a promising chassis organism for microbial electrosynthesis because it has a well‐defined biochemical pathway (the Mtr pathway) that can connect extracellular electrodes to respiratory electron carriers inside the cell. We previously found that the Mtr pathway can be used to transfer electrons from a cathode to intracellular electron carriers and drive reduction reactions. In this work, we hypothesized that native NADH dehydrogenases form an essential link between the Mtr pathway and NADH in the cytoplasm. To test this hypothesis, we compared the ability of various mutant strains to accept electrons from a cathode and transfer them to an NADH‐dependent reaction in the cytoplasm, reduction of acetoin to 2, 3‐butanediol. We found that deletion of genes encoding NADH dehydrogenases from the genome blocked electron transfer from a cathode to NADH in the cytoplasm, preventing the conversion of acetoin to 2, 3‐butanediol. However, electron transfer to fumarate was not blocked by the gene deletions, indicating that NADH dehydrogenase deletion specifically impacted NADH generation and did not cause a general defect in extracellular electron transfer. Proton motive force (PMF) is linked to the function of the NADH dehydrogenases. We added a protonophore to collapse PMF and observed that it blocked inward electron transfer to acetoin but not fumarate. Together these results indicate a link between the Mtr pathway and intracellular NADH. Future work to optimize microbial electrosynthesis in S. oneidensis MR‐1 should focus on optimizing flux through NADH dehydrogenases. Abstract : This study elucidates the role of NADH dehydrogenases in electron uptake from a cathode to drive intracellular acetoin reduction in Shewanella oneidensis .